Plan de marketing digital para la empresa JJ BIKES Atuntaqui, Imbabura, Ecuador. - Vega Jimenez, Juan José (2024)
This study employs a mixed-methods approach, combining qualitative and quantitative techniques, including customer surveys and interviews with the manager of JJ BIKES, as well as a SWOT analysis, to develop and evaluate a digital marketing plan aimed at improving JJ BIKES' strategic positioning in its target market by using digital media to increase brand visibility and recognition. The results indicate that implementing this plan can significantly enhance customer perception and preference, identifying effective strategies for promotion on social media and other digital platforms, which led to increased customer interaction and sales. It is concluded that a well-structured and executed digital marketing plan is crucial for JJ BIKES' growth and positioning in the current competitive market, providing a comprehensive understanding of the market and allowing for the creation of effective strategies. Keywords: digital marketing, marketing plan, marketing strategies, SWOT analysis, JJ BIKES, surveys, interviews.